Money Market Mechanism Based On Sharia Principles - Rahmawati Hutagalung (CV. AFDIFAL MAJU BERKAH, 2022)
The rapid development of economic activity followed by the development of financial institutions (banks) both conventional and using Islamic principles, in the banking world often use money market facilities in its operations, because in certain circumstances the bank may experience excess or lack of liquidity in the short term which is less than one year. The only money market that is allowed is the money market that does not use the interest system, this is to avoid riba nasi'ah because the loss (danger) of the interest is greater than the profit (mashlahah). In addition, because Islam prohibits the sale and purchase of money as a commodity or speculation. The National Sharia council should develop the concept of policies and procedures for money market activities in more detail, so that the parties to the transaction can comply with the principles of established Sharia norms. However, the fatwa of the National Sharia Council No:37/DSN-MUI/X/2002 can be used as a solution for parties (banks) that conduct transactions in the money market by providing alternative contracts mudharabah (muqaradhah), Musharakah, Qard, Wadiah, and al-Sharf.